Department of Obstetrics and Gynecology, SHKM Govt. Medical College Nalhar, Nuh, Haryana, India. (Journal of Forensic Medicine & Toxicology, 2023)
Medicolegal Autopsy is an integral part of assessment of cause of death in unnatural death. In India, conventional method of medicolegal post-mortem examination is widely acceptable method. Hence, Virtual autopsy may not become the alternative to Conventional autopsy, but it could be supportive and complimentary. Virtual autopsy a modern method and Conventional autopsy widely accepted method when both used together, it will definitely achieve the goal of more precise cause of death. Virtual autopsy is a minimally invasive, observer independent procedure that considers the use of various highly advanced imaging techniques and 3D construction software. The Virtual autopsy was implemented by University of Bern, Switzerland in mid1990. Later, it got recognized in countries like France, Germany, UK, Japan, Australia, the USA and Israel.
Keywords: Bengaluru; hospital; Virtual